EFFECT OF CURRENT RATIO (CR) AND DEBT TO EQUITY RATIO (DER) ON RETURN ON EQUITY (ROE): PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON EQUITY (ROE) - Rahayu Ning Tyas; Siti Fatonah; Surti Zahra (Yayasan Education and Social Center, 2021)
Companies that have a high level of profit reflect that the company has an excellent financial performance. The wise use of debt to finance the company's operations will have a good impact on the company, especially the company's owners (stakeholders). Conversely, if not appropriately managed, the use of debt will adversely affect the company's revenue. This study aims to determine the influence of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return On Equity (ROE) on companies producing raw materials of plantation sub-sectors listed on the Indonesia Stock Exchange for the period 2014-2019. Research methods used associative methods with a quantitative approach. The population in this study was 18 plantation companies. The samples used are as many as six plantation companies using purposive sampling techniques with consistent company criteria in publishing annual reports during the period 2014-2019. Test hypothetical test result t; the current ratio does not affect the return on equity obtained t calculated value -0.558 < t table -2.032. Hypothesis 2 test t, current ratio has no effect on debt to equity ratio obtained t calculated value 0.990 < t table 2.032. Simultaneously the current ratio and debt to equity ratio together do not affect the return on equity indicated by the value of Fhitung 1,042 < Ftabel 3.28. Partially and simultaneously, the current ratio and debt to equity ratio do not affect the return on equity in companies producing raw materials of plantation sub-sectors listed in IDX